D.F. Safonov. On the History of Soviet Diplomacy in Africa in the 1960s and 1970s - Ksenofontova Natalia Andreevna (Ученые записки Института Африки Российской академии наук)
2024 marks the 115th anniversary of the birth of the outstanding Soviet diplomat, D.F. Safonov, who contributed to the emergence and the shaping of international relations between the USSR and African countries, being the first ambassador of our country to Uganda (1963–1968) and Liberia (1972–1977). Having visited many countries of this continent and having worked in the African direction for 18 years, D.F. Safonov left several books of memoirs, rich in observations of the social and political life of the peoples of these states. His conclusions about the role of Russia in Africa and in international politics still sound very relevant today.